Short report: Patterns of US federal autism research funding during 2017–2019. (October 2021) - Harris, Lauren; Gilmore, Daniel; Longo, Anne; Hand, Brittany N
In 2017, the Interagency Autism Coordinating Committee, a federal advisory panel consisting of autism researchers and community members, recommended that funders of autism research prioritize research projects on: (1) treatments/interventions, (2) evidence-based services, and (3) lifespan issues. We sought to describe research funding since this recommendation was made. We searched the databases of the three largest federal funders of autism research in the United States (National Institutes of Health, Department of Education, and Centers for Disease Control and Prevention) for grants awarded during 2017–2019. We categorized grants as follows: autism screening and diagnosis, biology, risk factors, treatments and interventions, services, lifespan issues, or infrastructure and surveillance. We found that funding patterns remained largely consistent during 2017–2019. Biological research received a relative majority of funding (32.59%), followed by treatments and interventions (22.87%). While given higher funding priority by the Interagency Autism Coordinating Committee's recent budget recommendation, fewer funds were awarded to research areas like services (5.02%) and lifespan issues (2.51%), indicating a misalignment between funding patterns and the Interagency Autism Coordinating Committee budget recommendation. These findings emphasize the need for autism research funding to align with the Interagency Autism Coordinating Committee budget recommendations to best meet the needs of the autism community, particularly autistic younger, middle-aged, and older adults. Lay abstract: In 2017, an advisory board consisting of autism researchers and community members recommended that funders of autism research prioritize research projects on: (1) treatments/interventions, (2) evidence-based services, and (3) lifespan issues. To describe funding in these areas since this recommendation was made, we searched the databases of the three largest federal funders of autism research in the United States. We found that the largest portion of federal funding during 2017–2019 was awarded to research on the biology of autism (32.59%) and treatments and interventions for autism (22.87%). Less funds were awarded to research areas that are high funding priorities by the Interagency Autism Coordinating Committee budget recommendation including services (5.02%) and lifespan issues (2.51%). Our findings emphasize that autism research funding is not consistent with the Interagency Autism Coordinating Committee budget recommendation to increase funding particularly to services and lifespan issues. We recommend that funding patterns should shift to better align with these priorities so that autism research may better serve the needs of the autism community.